2022
DOI: 10.3389/fnagi.2021.789698
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis on the Genes and Their Interaction Underlying the Comorbidity of Alzheimer's Disease and Major Depressive Disorder

Abstract: BackgroundDuring the past years, clinical and epidemiological studies have indicated a close relationship between Alzheimer's disease (AD) and other mental disorders like major depressive disorder (MDD). At the same time, a number of genes genetically associated with AD or MDD have been detected. However, our knowledge on the mechanisms that link the two disorders is still incomplete, and controversies exist. In such a situation, a systematic analysis on these genes could provide clues to understand the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…The pathogenesis of Alzheimer’s disease (AD) is believed to be closely related to depression [ 106 , 107 ]. In particular, major depression and AD share biological processes and pathways, including 77 disease-related genes and 102 pathways [ 108 ]. Amyloid β (Aβ) is one of the vital shared pathogenic targets [ 109 , 110 , 111 , 112 ].…”
Section: Depression-associated Seh Promotes Liver Dysfunction and Bre...mentioning
confidence: 99%
“…The pathogenesis of Alzheimer’s disease (AD) is believed to be closely related to depression [ 106 , 107 ]. In particular, major depression and AD share biological processes and pathways, including 77 disease-related genes and 102 pathways [ 108 ]. Amyloid β (Aβ) is one of the vital shared pathogenic targets [ 109 , 110 , 111 , 112 ].…”
Section: Depression-associated Seh Promotes Liver Dysfunction and Bre...mentioning
confidence: 99%
“…Recent reports have revealed that there is a strong relationship between MDD and AD [18,19]. For example, a systematic analysis result revealed shared pathways and biological processes between MDD and AD and offered a hint for the comorbidity of MDD and AD [20]. Depression could act as a risk factor for the late development of AD [21].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of understanding arises partly from the structural and dynamic complexity of the systems involved and partly from the traditional approach of Western medicine, which tends to view health through the lens of isolated structural and functional elements rather than fully integrated dynamic systems. 8,9,10,11,12 To analyze effects of perturbations in these complex systems, we and others have developed network-and Information Theory-based methods to characterize underlying cause-effect relationships. 13,14,15,16,17,18 These approaches provide valuable insights into comorbidities and their impact on health.…”
Section: Introductionmentioning
confidence: 99%